2002
DOI: 10.1111/j.1365-2621.2002.tb09443.x
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Extraction From Shrimp Waste by Lactic Fermentation and Enzymatic Hydrolysis of the Carotenoprotein Complex

Abstract: Natural carotenoids are an alternative to synthetic orange-red pigments. They are present in crustaceans as a protein-pigment complex. In order to extract this highly unstable pigment, crustacean waste must be stabilized; lactic fermentation is a simple and environmentally friendly method to achieve this goal. Shrimp wastes were inoculated with Lactobacillus bacterial cultures. Carotenoids were then extracted with an organic solvent system. Protein-pigment splitting was carried out using a mixture of 4 commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 23 publications
1
48
0
2
Order By: Relevance
“…The small peaks recorded at the end of the profile presumably corresponded to oxidized forms of astaxanthin. In fact, similar results (presence of small peaks) were reported by Armenta-Lopez et al [37].…”
Section: Recovery After Carotenoprotein Enzymatically Hydrolysis Of Asupporting
confidence: 89%
“…The small peaks recorded at the end of the profile presumably corresponded to oxidized forms of astaxanthin. In fact, similar results (presence of small peaks) were reported by Armenta-Lopez et al [37].…”
Section: Recovery After Carotenoprotein Enzymatically Hydrolysis Of Asupporting
confidence: 89%
“…As a substitute to the chemical and enzymatic processes, fermentation, combining deproteinization and demineralization, has been evaluated as an eco-friendly and positive procedure [14]. Furthermore, fermentation represents a cheap technique which will stabilize and retain the nutritional quality of by-products [15].…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of astaxanthin from shrimp by-products can be combined with chitosan production (Armenta-Lopez et al 2002) and some studies have shown that acids, commonly used in the chitosan industry, may increase the yield of astaxanthin because of reduced oxidation. However excessively aggressive acid and alkali treatments can Capsules of "natural" astaxanthin containing around 4mg per capsule from H. pluvialis commonly sell for around US$20 for 60 on the internet, therefore there is commercial potential for a natural substance from a number of aquaculture sources including shrimp and salmon by-product (Pacheco et al 2009;Synowiecki and Al-Khateeb 2000).…”
Section: Carotenoids (Astaxanthin and Canthaxanthin)mentioning
confidence: 99%